Drafting effect in cycling: investigation by wind tunnel tests - Belloli, M.; Giappino, S.; Robustelli, F.; Somaschini, C. (Procedia Engineering, 2016)
Cyclists travelling in groups experience a significant reduction in the wind resistance and those behind consume less energy due to the shielding effect of the front cyclist. We investigated drafting effects by wind tunnel tests realizing a test set-up with two cyclists pedalling at different longitudinal distance. Drag reduction effects on both the leading and the trailing cyclist are confirmed. The presence of lateral wind is also investigated showing a significant reduction of the drafting effect also for light winds.